INTERVENSI PHARMACY COACHING OLEH MAHASISWA FARMASI UNTUK PERBAIKAN TINGKAT KEPARAHAN ADIKSI PADA PASIEN NAPZA RAWAT JALAN - Alexxander Alexxander; Ika Puspitasari; Susi Ari Kristina; Cecep Sugeng Kristanto (Jurnal Ilmiah Ibnu Sina (JIIS): Ilmu Farmasi dan Kesehatan, 2020)
Napza is a substance or drug that affects the body, especially the central nervous system, causing psychological disorders and social functions due to habits, addiction (addiction) and dependence. Pharmacy coaching emphasizes two-way communication tailored to the uniqueness of the individual. Pharmacy coaching interventions have the potential to reduce the severity of addiction in outpatient drug rehabilitation patients. The aim of this study was to determine whether there was an improvement in the severity of addiction in Napza outpatient who received pharmacy coaching intervention by pharmacy students. This research method is one group pretest-posttest design using primary and secondary data. The study was conducted in February - April 2020, at the Sambang Lihum Mental Hospital, South Kalimantan. Population are NAPZA rehabilitation patients undergoing outpatient treatment, sampling using consecutive sampling method, which meets the inclusion and exclusion criteria. Tools and instruments are data collection sheets, in the form of patient characteristics data sheets and WHO ASISST V3.0 questionnaire. Data were analyzed with SPSS version 16.0 using parametric paired t-test. Based on the research, the results showed that pharmacy coaching interventions in outpatient NAPZA by pharmacy students, proved significant improvements to the severity of addiction. The results of pre-intervention and post-intervention value respectively were 59.75 and 19.75, with a difference in the decrease (ÃƒÅ½Ã¢â‚¬Â) 40 points (P = 0.001).